Cervical intraepitheial neoplasm with ichthyosis uteri- A case report - Malla Vaidya, Karishma; Shrestha, Bigya (Journal of Pathology of Nepal, 2018)
A rare condition in which the entire surface of the endometrium is replaced by stratified squamous epithelium is called Ichthyosis uteri. Originally described as an endometrial response to iatrogenically-introduced caustic substances, similar changes have since been described in association with a variety of inflammatory conditions of the endometrium. Here we report a case of intraepithelial neoplasm III, with ichthyosis uteri. A 75-years-old female with hypetension, underwent total abdominal hysterectomy with bilateral salphingo-ophorectomy for watery discharge per vaginal since four months.